Enjoying value-added products of apple pomace - Sharma, R R; Sharma, Swati; Reddy, Vijay R; Krishna, K Rama; Prasad, K (Indian Horticulture, 2019)
The apple pomace is a waste generated by apple juice processing industries, which is usually dumped outside factories or in running water where it acts as a major source of pollution in water and air. In India, about 5,000 tonnes of apple pomace is produced, which merely goes waste, whereas it is a good source of several vital elements. The technologies have been standardized world over for its effective utilization for the development of several value-added products like jam and jelly, pectin, ethanol, citric acid, vinegar and animal feed. Thus, we can save our environment and huge foreign exchange, which our country spends on importing such products from several countries.